The Role of the Fishing Sector in the Blue Economy: Prioritization, Environmental Challenges, and Sustainable Strategies in Europe, with a Focus on Spain - Nicoletta González-Cancelas; Javier Vaca-Cabrero; Alberto Camarero-Orive (Journal of Marine Science and Engineering)
The fishing sector is a key component of the European Blue Economy, contributing to economic growth, food security, and employment. However, it faces sustainability challenges, including overfishing, biodiversity loss, and climate change impacts. This study uses decision tree modeling to assess the sector’s prioritization within the Blue Economy, comparing its economic and environmental footprint to other maritime industries. Using EU Fleet Register data, findings reveal disparities in fleet modernization and efficiency, with industrialized fleets in Spain, France, and Italy exhibiting higher tonnage and power, while artisanal fisheries in Greece and Portugal remain more vulnerable to economic and environmental shifts. The study highlights the sector’s economic relevance but also its exposure to regulatory constraints, emphasizing the need for modernization and stricter sustainability policies. The paper proposes technological innovation, enhanced regulations, and conservation-based management to align fisheries with Sustainable Development Goal 14, the EU Common Fisheries Policy, and the European Green Deal. These insights provide data-driven strategies for policymakers and industry stakeholders to ensure a more sustainable and resilient fishing sector.